Impact of Seismic Data Processing on Exploration Efficiency: Case Studies from OML 29 Projects to Improve Exploration Practices and Success - Nyaknno Umoren; Malvern Iheanyichukwu Odum; Iduate Digitemie Jason; Dazok Donald Jambol (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
This review investigates the transformative role of seismic data processing in enhancing exploration efficiency, with a specific focus on case studies drawn from the OML 29 oil block in Nigeria. As exploration targets grow increasingly complex, the accuracy and resolution of seismic imaging have become pivotal to reducing drilling risks and improving subsurface characterization. The paper reviews various data processing workflows, including noise attenuation, velocity modeling, multiple suppression, and pre-stack depth migration, evaluating their contributions to hydrocarbon prospect identification in the OML 29 region. Additionally, it discusses the impact of integrating advanced processing techniques—such as full waveform inversion and machine learning-driven denoising algorithms—on improving data fidelity and decision-making. The analysis leverages real-world exploration outcomes within OML 29 to highlight best practices, technological gaps, and operational lessons. By synthesizing technical findings and project performance data, this study outlines actionable recommendations for optimizing seismic workflows, reducing uncertainty, and increasing the success rate of exploration campaigns. Ultimately, the paper aims to support geoscientists, data processors, and exploration managers in leveraging seismic data processing as a strategic tool to unlock greater economic and technical value in hydrocarbon exploration projects.
Keywords: Seismic Data Processing; Exploration Efficiency; OML 29; Subsurface Imaging; Hydrocarbon Exploration